2017
DOI: 10.1590/0001-3765201720150536
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenotoxicity of rice crop water after application of the tricyclazole fungicide

Abstract: Tricyclazole is currently one of the fungicides recommended for the treatment of diseases in irrigated rice. However, there is relatively little information on its cytotoxic and genotoxic potential. The objective of this study was to evaluate the cytotoxicity and genotoxicity of rice crop water after apllication of the tricyclazole fungicide through the Allium cepa L. test. The rice crop water samplings were collected before and 1, 15 and 30 days after application of the fungicide in rice plant shoots. The All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
3
0
6
Order By: Relevance
“…The studied pesticides had practically no effect on the MI of the root apex meristem of 2-day-old wheat seedlings. A similar lack of cytotoxic effect of the tricyclazole fungicide tricyclazole used in rice cultivation is described by Wandscheer et al [23]. Using the Allium cepa test, the authors showed, that tricyclazole causes chromosomal abnormalities, but does not signi cantly affect the MI.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The studied pesticides had practically no effect on the MI of the root apex meristem of 2-day-old wheat seedlings. A similar lack of cytotoxic effect of the tricyclazole fungicide tricyclazole used in rice cultivation is described by Wandscheer et al [23]. Using the Allium cepa test, the authors showed, that tricyclazole causes chromosomal abnormalities, but does not signi cantly affect the MI.…”
Section: Discussionsupporting
confidence: 65%
“…For example, the systemic fungicide Tricyclazole, used on irrigated rice crops, has genotoxic activity: increases the frequency of chromosomal abnormalities [23]. The systemic herbicide Roundup, used to control weeds in cereal crops, increases the number of metaphase disorders in barley, which is due to the negative effect on the mitotic spindle formation [24].…”
Section: Introductionmentioning
confidence: 99%
“…The Allium cepa roots were placed in contact with rice crop water to check for possible chromosomal MI abnormalities by Wandscheer et al (2017). The data obtained indicates that the application of the tricyclazole fungicide leads to an increase in the genotoxic activity in the rice crop water, through the appearance of chromosomal abnormalities, without, however, causing significant effects on the MI.…”
Section: Cyto-genotoxicity Of Fertilizers Monitored By Allium Root Timentioning
confidence: 99%
“…One of the possibilities for studying the genotoxic effect of pesticides is using plants as test objects. Plants are recognized as excellent genetic models in detecting mutagenic environmental agents and are often used for biomonitoring studies [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%